Utilization of KIA Books on Pregnant Women's Knowledge About The Dangers of Pregnancy at The Buntulia Community Health Center - Sasmita Bangga; Widiatrilupi, Maria; Anik Purwati (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
The Maternal and Child Health (KIA) Book is an important media used to provide health information for pregnant women. Effective utilization of the KIA Book can increase pregnant women's knowledge about the dangers of pregnancy, thus supporting a healthy pregnancy. However, not all pregnant women have utilized the KIA Book optimally, especially in the UPTD Buntulia Health Center area. This study aims to analyze the utilization of the KIA Book on the level of knowledge of pregnant women about the dangers of pregnancy in the UPTD Buntulia Health Center. This study used a quantitative analytical design with a cross-sectional approach. Respondents were 16 pregnant women selected by purposive sampling. Data were collected through a structured questionnaire and analyzed using the chi-square statistical test. The results showed that there was a significant relationship between the utilization of the KIA Book and the level of knowledge of pregnant women about the dangers of pregnancy (p-value = 0.000). Pregnant women who actively utilize the KIA Book tend to have a better level of knowledge than those who do not utilize it. Optimal utilization of the KIA Book contributes positively to increasing pregnant women's knowledge about the dangers of pregnancy. It is recommended that health workers at Buntulia Health Center be more active in providing education on the importance of using the KIA Book and providing assistance to pregnant women to maximize its benefits